Predictors of periodontal diseases in the student population of caucasus international university: A study of risk factors and oral health optimization - Lela Tsitaishvili; Tamar Jikia (Wolters Kluwer Medknow Publications, 2023)
Introduction: Periodontal diseases cause esthetic and functional disorders having an impact on oral and general health and the psychological and social status of a person. "Unhealthy oral cavity" as a problem is particularly painfully perceived by young patients, having concern predominantly about their appearance and personal social connections. The migration of foreigners to Georgia has made a great impact on dental referrals in Georgia last years. Foreign populations are different in lifestyle, diet, dental practices, and oral hygiene habits. They live, study, or work and are closely integrated into Georgian society; subsequently, their oral health may influence periodontal diseases' overall prevalence in the country. The Aim of the Study: The aim of this study was to assess the periodontal status of Caucasus International University (CIU) students of different nationalities, study the risk factors, and oral health optimization by planning and implementing preventive measures. Methods: This was randomized research conducted on 820 students aged 18-35 years, including 370 Georgians and 450 foreigners, 369 boys and 451 girls. Results: Unhealthy periodontal tissues were observed in 46.3% of boys and 44.6% of girls. 34.8% of Georgians and 66.4% of foreigners were suffering from gum bleeding. Bleeding on probing of II and III degrees was common in the 1st (18-25) age group (40.5% and 31.0%, respectively) and I and II degrees in the 2nd (26-35) age group (39.4% and 44.9%, respectively). Conclusion: Findings indicate a rather high prevalence of dental plaque-induced gingivitis in the CIU student population. Students do not receive adequate dental care and have negative attitudes toward oral hygiene skills and dental services. Management of periodontal problems with an emphasis on oral hygiene enhancement and promotion of oral prophylaxis accentuated the role of the university dental clinic in providing scientific and clinical experience to the CIU students.